Management Information Systems In Private Universities and Its Impact On Productivity - Rika Nurhidayah; Dadah Muliansyah (CV Putra Publisher, 2023)
Because of its efficiency and efficacy, the use of information technology in school management has grown rapidly. The primary goal of management information systems (MIS) in their early phases was to improve the efficiency of school and office activities. Overall, a review of the literature revealed that MIS has a positive impact on school administration and management, including improved information accessibility, more efficient administration, higher utilization of school resources, reduced workload, better time management, and improved report quality. Despite all of the advancements in educational management, most educational institutions face various obstacles, particularly in the field of information and communications technology. Among other things, a study into Management Information Systems and their impact on productivity in higher education institutions was conducted to examine the relevance of MIS in improving educational management, assess ways MIS could improve capacities in data processing, storage, analysis, and the timely supply of educational information to management and administrators to enhance quick and efficient decision making. The major sample strategies used were stratified and purposive sampling. To collect pertinent data, a questionnaire and an observational program were utilized. The data was analyzed using the Statistical Package for Social Sciences (SPSS version 25). According to the study, the key barriers militating against the introduction of MIS in understudy institutions were cost, a lack of competent Information Technology people to administer the system, a shortage of computer systems and peripherals, and an inferiority mentality (technology phobia). Recommendations, as well as proposals for additional research, were thus made to address the issues discovered.